2017
DOI: 10.1186/s13065-017-0296-y
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high resolution X-ray structures of two forms of human recombinant insulin at 100 K

Abstract: The crystal structure of a commercially available form of human recombinant (HR) insulin, Insugen (I), used in the treatment of diabetes has been determined to 0.92 Å resolution using low temperature, 100 K, synchrotron X-ray data collected at 16,000 keV (λ = 0.77 Å). Refinement carried out with anisotropic displacement parameters, removal of main-chain stereochemical restraints, inclusion of H atoms in calculated positions, and 220 water molecules, converged to a final value of R = 0.1112 and Rfree = 0.1466. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…These water molecules, along with three His-10 residues per Zn 2+ ion, create an octahedral coordination shell around the ion (Figure a inset). However, reports of tetrahedral arrangements (with three His-10 and one water) are also available in the literature. In our simulations, the octahedral geometry is preserved throughout the 100 ns trajectory, indicating a very stable coordination geometry. Thus, we ask the question, how stable is this complex?…”
Section: Resultsmentioning
confidence: 64%
“…These water molecules, along with three His-10 residues per Zn 2+ ion, create an octahedral coordination shell around the ion (Figure a inset). However, reports of tetrahedral arrangements (with three His-10 and one water) are also available in the literature. In our simulations, the octahedral geometry is preserved throughout the 100 ns trajectory, indicating a very stable coordination geometry. Thus, we ask the question, how stable is this complex?…”
Section: Resultsmentioning
confidence: 64%
“…S7(a)-7(c) (see supporting information) show the ratio of temperature B-factor values for the S /C atoms of cysteines involved in the disulfide bonds calculated as described in the Materials and methods section (x2) for the lysozyme, proteinase K and insulin structures presented herein, and for several structures deposited in the PDB, i.e. 6qqe (Gotthard et al, 2019), 1qio (Weik et al, 2000), 1iee (Sauter et al, 2001) and 6ftr (Wiedorn et al, 2018) for lysozyme, 2pwa (unpublished results), 5kxu (Masuda et al, 2017) and 1ic6 (Betzel et al, 2001) for proteinase K, and 4f1g (Fa ´vero-Retto et al, 2013) and 5e7w (Lisgarten et al, 2017) for insulin. These PDBs were selected based on the relevance of the experimental conditions at which the crystal structures were collected, such as the temperature of data collection, the sample delivery method used and the X-ray radiation source.…”
Section: Site-specific Radiation Damagementioning
confidence: 99%
“…The intra-chain disulfide bond of Cys6-Cys11 of recombinant insulin was reported to affect the chain flexibility. 30 It has also been shown that the disulfide bond formation and disruption regulate the angiotensin release. 31 The transition of angiotensinogen under oxidative environment to its more active form with sulphydryl-bridged plays an important role in pregnancy hypertension and pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%